Regulatory impact assessment and “regulatory guillotine” as institutional forms of business community’s participation in the improvement of regulatory framework in Russia - A. A. Lialikov (Вестник университета, 2022)
The article examines the forms of participation of the business community in the modernization of the regulatory framework in Russia from the perspective of formal procedures provided by the Russian system of public administration. The objects of the study are the institution of regulatory impact assessment (RIA) and the mechanism of “regulatory guillotine”. The aim of the study is to conduct a comparative analysis of the RIA procedure and the mechanism of “regulatory guillotine”. The methodology of the study is based on the methods of comparative and structural-functional analysis of normative legal acts containing the procedures. The article provides a analysis of procedures, presents the legal basis and their functional roles in the system of state decision-making, identifies the objects of influence and stages of procedures, identifies access points and the degree of representation of the business community. The implementation of the procedures contributes to the transparency of the public administration system of Russia, ensuring the development of institutions for the participation of industry experts on the part of the business community in decision-making on issues of regulatory framework. At the same time, the mechanism of the “regulatory guillotine” has a higher degree of influence on the process of approval of draft normative legal acts, but at the same time it is less representative than the regulatory impact assessment procedure.